2019
DOI: 10.3844/ajeassp.2019.173.184
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Remediation of Water Quality in Monitoring Potential of Acid Mine Drainage

Abstract: Acid Mine Drainage (AMD) associated with both active and abandoned mining operations related to sulfide minerals, oxidation of pyrite affording an acidic solution that contains toxic metal ions. Result shows that pH value of water in Kg. Aur, Chini and Sg. Lembing are acidic with value of 2.81, 4.16 and 3.60 respectively. Maximum concentrations of heavy metals in the study area are: Pb (0.2 mg/L), Cd (0.05 mg/L), Zn (5.1 mg/L), Cu (5.2 mg/L), Mn (10.9 mg/L), Cr (0.2 mg/L), Ni (0.2 mg/L), As (0.005 mg/L) and Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Table 2 shows the sources of AMD [21,29]. In Malaysia, certain mines encounter AMD issues, especially occurring in abandoned mines [30,31,32,33,34]. Table 3 shows the mines in Malaysia that have issues with AMD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows the sources of AMD [21,29]. In Malaysia, certain mines encounter AMD issues, especially occurring in abandoned mines [30,31,32,33,34]. Table 3 shows the mines in Malaysia that have issues with AMD.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 shows the mines in Malaysia that have issues with AMD. [30,31,32,33,34]. A Previous study had shown that commercial quicklime and CL were used to treat AMD from an active tailing pond in Perak, Malaysia [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation